KITAPQUMARLÍQ MÁDENIYATÍN QÁLIPLESTIRIWGE QARATÍLǴAN KÓZQARASLAR - Ilyasova, Z.U. (SCIENCE and SOCIETY, 2025)
This article examines the role of reading culture in society and individual life, effective methods for its formation, and modern approaches. It discusses ways to instill a love for books in students during the educational process, develop reading culture, and explores the role of family and school environments in this regard. Furthermore, the article provides suggestions for utilizing information and communication technologies to promote reading habits.